Development of Student Worksheets Based on Generic Science Skills on the Concept of Acid and Base - Putri Hasibuan, Nur Azizah; Hasibuan, Rafikah Rezky (LAVOISIER: Chemistry Education Journal, 2022)
This research is supposed to develop generic science skill-based student worksheets on chemistry learning materials acid and based. The method used in this research is the following ADDIE models (Analysis, Design, Develop, Implementation, and Evaluation). In the implementation step, the worksheet was used on 11th grade of South Tangerang Banten, Indonesia, general high school which was followed by 29 students. The instrument used is a questionnaire to measure the feasibility of the worksheet by experts (lecturer and teacher), and also student questionnaire response sheets. The findings of this research can conclude that the feasibility in terms of design component, appearance, content, language, and worksheet's appropriate with generic science skills. And the student responses, respectively for 84.13%; 92.26%; 92.41%; 95.95%; and 86.9%. This result shows that generic science skill-based worksheets can be used for the learning process. But still need to develop for bigger responders.